Diary of a survivor nineteen years in a Cuban women's prison - Rodríguz, Ana; Garvin, Glenn (St. Martin's Press, 1995)
"A personal account of life in prison by an early opponent of the Castro regime. Written as a testimonial and memoir, it documents the sordid abuses visited upon female prisoners in Castro's jails. One of the very few accounts of its kind, it is part of a genre that probes resistance to dictatorship. Offers details of how Castro's propaganda machine attempts to turn opponents of communism into outcasts"--Handbook of Latin American Studies, v. 57.. - http://www.loc.gov/hlas/